2010
DOI: 10.1038/onc.2010.421
|View full text |Cite
|
Sign up to set email alerts
|

Vimentin is a novel AKT1 target mediating motility and invasion

Abstract: The PI3K/AKT signaling pathway is aberrant in a wide variety of cancers. Downstream effectors of AKT are involved in survival, growth, and metabolic-related pathways. In contrast, contradictory data relating to AKT effects on cell motility and invasion, crucial pro-metastatic processes, have been reported pointing to a potential cell type and isoform type-specific AKT driven function. By implication, study of AKT signaling should optimally be conducted in the appropriate intracellular environment. Prognosis in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
177
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(182 citation statements)
references
References 40 publications
2
177
0
Order By: Relevance
“…Furthermore, p-vimentin expression levels decreased after enoxaparin 1 gefitinib treatment to some extent as a result of the inhibition on tumor cell migration by DOCK1. Furthermore, in our DOCK1 siRNA studies, p-vimentin expression, which has been shown to enhance tumor and metastasis growth (Zhu et al, 2011), was reduced in accordance with the siRNA-mediated inhibition of DOCK1 expression.…”
Section: Sensitization Of Lung Cancer Cells By Enoxaparin To Gefitinibsupporting
confidence: 68%
See 1 more Smart Citation
“…Furthermore, p-vimentin expression levels decreased after enoxaparin 1 gefitinib treatment to some extent as a result of the inhibition on tumor cell migration by DOCK1. Furthermore, in our DOCK1 siRNA studies, p-vimentin expression, which has been shown to enhance tumor and metastasis growth (Zhu et al, 2011), was reduced in accordance with the siRNA-mediated inhibition of DOCK1 expression.…”
Section: Sensitization Of Lung Cancer Cells By Enoxaparin To Gefitinibsupporting
confidence: 68%
“…The binding of Akt to vimentin results in vimentin phosphorylation, enhancing the ability of vimentin to induce motility and invasion while protecting vimentin from caspase-induced proteolysis (Zhu et al, 2011). Thus, it can be speculated that the more effective inhibitory effect on pvimentin produced by enoxaparin 1 gefitinib involves control of the Akt pathway in NSCLC A549 cells.…”
Section: Sensitization Of Lung Cancer Cells By Enoxaparin To Gefitinibmentioning
confidence: 99%
“…4). This EMT program is recapitulated with respect to IF protein composition when cancerous cells become metastatic (53,54), and importantly, it has been shown that vimentin expression is required for the invasive behavior of prostate and breast cancer cells (55)(56)(57). Further evidence that vimentin IFs play a key role in regulating mesenchymal cell shape and motility comes from studies in which vimentin is experimentally reorganized in human foreskin fibroblasts by expressing a dominant negative mutant to disrupt vimentin IF assembly or by downregulation following silencing of vimentin expression with shRNA.…”
Section: Changes In Vimentin If Network Composition and The Epitheliamentioning
confidence: 99%
“…AKT1 kinase binds to and phosphorylates vimentin at serine 39, which prevents vimentin from caspase-induced proteolysis, leading to increased motility and invasiveness of soft-tissue sarcoma cells. Moreover, vimentin phosphorylation was shown to enhance tumor and metastasis growth in vivo (20). Vimentin has also been reported to be a downstream target of PI3Kg signaling, the activation of which results in increased vimentin phosphorylation that is required for efficient cellular migration (1).…”
Section: Vimentin: Regulation Of Signaling Pathways and Tumorigenesismentioning
confidence: 99%